Dampak Virus Covid-19 pada Pelaksanaan Pendidikan Jasmani di SMA N 2 Semendawai Barat Tahun Ajaran 2021/2022 - Tridamel Andriansyah; Ilham Arvan Junaidi; Jujur Gunawan Manulang (Journal on Education, 2023)
Covid-19 is a deadly virus that attacks the human respiratory system and is transmitted by splashing saliva (drops). The existence of the Covid-19 pandemic has made conventional face-to-face learning no longer possible in various regions.This study aims to analyze the impact of the Covid-19 virus pandemic on the implementation of physical education learning at SMA N 2 Semendawai Barat.The research method used in this study was a descriptive method. The data analysis technique used in this study was a questionnaire in the form of a questionnaire consisting of 15 questions. The sample in this study was 12th grade students at SMA N 2 Semendawai Barat. Then, to analyze the writer used Likert scale, data analysis using quantitative descriptive analysis techniques.The results of the research that the authors conducted showed that there were positive and negative impacts caused by the Covid-19 pandemic on the implementation of physical education at SMA N 2 Semendawai Barat found a very high percentage of 5%, high category 80%, while the other categories were medium categories of 10%, the low category was 5%, and the very low category was 5%..Based on the results of the analysis and conclusions in the discussion chapter, the authors provide the following suggestions: For educational institutions, it is hoped that they will be able to utilize the results of this research as a reference and additional knowledge. For teachers, it is expected that teachers will be more creative and innovative in providing learning materials so that students are more enthusiastic about participating in learning, For Further Researchers It is hoped that it will be able to become a reference for further research and be able to be developed so that it becomes even better research.